Exploration of Methods for Slope Stability Analysis Influenced by Unsaturated Soil - Mohd Fakhrurrazi, Ishak; Muhammad Farhan, Zolkepli (Oklahoma State University, 2016)
This study will lead to the analysis of unsaturated soil using Bishop’s Simplified method (1955) which is one method to analyze slope stability in method of slices. In this study, the original formula for Bishop’s Simplified method (1955) of saturated soil were modified by adding the element of matric suction, )(waμμ− together with unsaturated friction angle, bφ which is applicable for the analysis of unsaturated soil. In this study, 0 kPa, 20 kPa and 40 kPa of matric suctions were applied in the analysis for both methods. From the analysis, the result indicate that the factor of safety (FOS) value of Bishop’s Simplified method (1955) was 7.65 % higher than Fellenius’s method for 0 kPa suction, which mean that the soil is in saturated condition. For 20 kPa suction, the FOS of Bishop (1955) was 4.83 % higher than Fellenius (1936). Bishop (1955) also gave higher FOS value compare to Fellenius (1936) by 4.41 % for 40 kPa suction. It can be concluded that, the reason for the relative accuracy of the Bishop’s Simplified method (1955) is that in considering only the vertical equilibrium of any slice, there is no need to account for the horizontal components of the inter-slice forces.